Activation of the feline umami receptor fT1R1-fT1R3 by linear α-L-dipeptides: an in vitro study - Hernangomez de Alvaro, Carlos Juan (2017)
Cats (Felis catus) are obligate carnivores and as such they are adapted to detect the taste of meat and its components, such as L-amino acids, which generate umami (or savoury) taste, analogous to the taste of MSG for humans. The umami taste receptor (T1R1-T1R3) plays an important part in the oral detection of L-amino acids by cats and other mammals. Cats can perceive all of the L-amino acids in vivo, however not all of them activate the feline umami receptor in vitro. Proteins are formed from long chains of L-amino acids bound together, which in turn can be broken down into smaller fragments or peptides through processes such as hydrolysis and fermentation. These processes are often necessary to increase the flavour, nutritional value, digestibility and hypoallergenicity of proteins used in manufacture of pet food. The aim of this research project was to determine if the dipeptides formed by the combination of the 11 umami-active L-amino acids for cats (Ala, Asn, Cys, Gly, His, Leu, Met, Phe, Ser, Trp and Tyr) were also umami-active using a cell-based cat umami taste receptor assay. The results identified that, from the library of 101 α-L-dipeptides tested, only three were active (Gly-Cys, Phe-Leu and Tyr-Gly), but had a weaker interaction with the receptor than the component L-amino acids (maximum 20-50% of activation). An unusual in vitro response pattern was found for several of the dipeptides, which was attributed to non-specific responses or interactions. Using an in silico model of the cat umami receptor, the reduction in the binding interaction of the dipeptides was proposed to be due to the increase in their zwitterionic dipole length compared to the individual L-amino acids. This made it more difficult to stabilise the closed (active) conformation in the Venus flytrap region (active binding site) of the T1R1 subunit of the cat umami receptor. This research helps to further elucidate the role of dipeptides on umami taste perception of cats.